2020
DOI: 10.1029/2020gc009380
|View full text |Cite
|
Sign up to set email alerts
|

Authigenic Ferrimagnetic Iron Sulfide Preservation Due to Nonsteady State Diagenesis: A Perspective From Perseverance Drift, Northwestern Weddell Sea

Abstract: • Magnetic mineral diagenesis is studied in Antarctic sediments using high-resolution porewater and rock magnetic data • Magnetic mineral dissolution and authigenesis is tightly coupled to dissolved sulfide and ferrous iron concentrations • Remanence-bearing iron sulfides form below the sulfate-methane transition and can be preserved following nonsteady state diagenesis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
(194 reference statements)
0
7
0
Order By: Relevance
“…This may not be surprising if the concentrations reflect the degree of dissolution during reductive diagenesis, as it is often observed that hematite is more resistant to dissolution than magnetite (Dillon & Bleil, 2006; Garming et al., 2005; J. Liu et al., 2004; Poulton et al., 2004; Reilly et al., 2020; Yamazaki et al., 2003). However, we also note a few anomalously high HIRM values in the U1538 stratigraphy without corresponding increases in other concentration dependent parameters, which are reminiscent of horizons with increased authigenic iron sulfide preservation that saturate above 300 mT, such as 3C pyrrhotite (Reilly et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This may not be surprising if the concentrations reflect the degree of dissolution during reductive diagenesis, as it is often observed that hematite is more resistant to dissolution than magnetite (Dillon & Bleil, 2006; Garming et al., 2005; J. Liu et al., 2004; Poulton et al., 2004; Reilly et al., 2020; Yamazaki et al., 2003). However, we also note a few anomalously high HIRM values in the U1538 stratigraphy without corresponding increases in other concentration dependent parameters, which are reminiscent of horizons with increased authigenic iron sulfide preservation that saturate above 300 mT, such as 3C pyrrhotite (Reilly et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic mineral authigenesis is largely controlled by porewater geochemistry, particularly through the production of dissolved Fe 2+ during Fe 3+ reduction and the production of H 2 S during SO 4 2− reduction (Amiel et al., 2020; Berner, 1984; Canfield & Berner, 1987; Karlin & Levi, 1983; Reilly et al., 2020). The order in which electron acceptors are used in microbial respiration is governed by their energetic favorability (Froelich et al., 1979), with Fe 3+ being more energetically favorable than SO 4 2− .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, relatively lower values of SIRM/χ lf (Figure 3e) followed by a consistent trend in the majority of the samples (except in Khandepar River) suggest that early reductive diagenesis has minimal impact on the Mandovi estuarine sediments. This can be explained by the fact that an enormous supply of detrital iron oxides from fluvial sources to the Mandovi estuary might have hindered the diagenetic reactions and hence the detrital magnetic particles were less affected by dissolution and remained preserved (Amiel et al, 2020;Gaikwad et al, 2021;Kao et al, 2004;Reilly et al, 2020). Biogenic magnetic particles synthesized by magnetotactic bacteria are ubiquitously found in estuarine environments (Hilgenfeldt, 2000;Hounslow & Maher, 1996;Kirschvink & Chang, 1984;Kopp & Kirschvink, 2008;Petersen et al, 1986;Roberts, 2015;Stolz et al, 1986).…”
Section: A Magnetic Proxy For Tracing Riverbank Erosionmentioning
confidence: 99%